Pengaruh Human Relation, Lingkungan Kerja Fisik, dan Iklim Organisasi terhadap Kinerja Pegawai pada Bidang Pembinaan SMA Disdikpora Provinsi Bali - Dipayana, Putu Eka; Kusyana, Dewa Nyoman Benni (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Employee performance is a crucial issue in achieving organizational goals. Every organization, whatever its goals, whether profit or non-profit oriented, will need employees who are able to show the best performance. Employee performance can be influenced by many factors, including human relations, physical work environment, and organizational climate. The aim of this research is to determine the influence of human relations, physical work environment, and organizational climate on employee performance in the Bali Province Education and Youth Department High School Development Sector. The research population was 30 employees. The sampling technique uses a census. Data collection was carried out using interviews, questionnaires and documentation methods. The analysis technique used is multiple linear regression. The results of the analysis prove that human relations, the physical work environment and organizational climate have a positive and significant effect on employee performance, thus partially. Suggestions given include increasing employee cooperation such as holding gatherings, adding lighting to the work space, and giving awards to outstanding employees such as providing promotion opportunities.